Hardware developments of an ultrasonic tomography measurement system - Hudabiyah, Arshad Amari; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Herlina, Abd Rahim; Pusppanathan, Muhammad Jaysuman (International Frequency Sensors Association (IFSA), 2012)
Link to publisher's homepage at http://www.sensorsportal.com/